Organ damage accrual and distribution in systemic lupus erythematosus patients followed-up for more than 10 years. (October 2017) - Taraborelli, M; Cavazzana, I; Martinazzi, N; Lazzaroni, M Grazia; Fredi, M; Andreoli, L; Franceschini, F; Tincani, A
Objective: The aim of this study was to determine the prevalence, predictors and progression of organ damage in a monocentric cohort of systemic lupus erythematosus patients with a long follow-up. Organ damage was assessed by the Systemic Lupus International Collaborating Clinics Damage Index one year after diagnosis and every five years. Disease activity was measured by the systemic lupus erythematosus disease activity index (SLEDAI)-2K at the beginning of the follow-up. Univariate and multivariable analyses were used to detect items associated with damage. A total of 511 systemic lupus erythematosus patients (92% females, 95% Caucasian), prospectively followed from 1972 to 2014, were included. Results: After a mean disease duration of 16 years (SD: 9.5) and a mean follow-up of 12.9 years (SD: 8.8), 354 patients (69.3%) had accrued some damage: 49.7% developed mild/moderate damage, while 19.5% showed severe damage. Damage was evident in 40% of 511 patients one year after diagnosis, and its prevalence linearly increased over time. Longer disease duration, higher SLEDAI, severe Raynaud's, chronic alopecia and cerebral ischaemia were significantly associated with organ damage. No associations between damage and autoantibodies, including anti-dsDNA, anti-Sm or antiphospholipid antibodies, were observed. Anyway, antiphospholipid syndrome and anticardiolipin antibodies predicted the development of neuropsychiatric damage. The ocular, musculoskeletal and neuropsychiatric systems were the most frequently damaged organs, with a linear increase during follow-up. Conclusion: A high rate of moderate and severe damage has been detected early in a wide cohort of young lupus patients, with a linear trend of increase over time. Disease activity and long duration of disease predict damage, while antiphospholipid antibodies play a role in determining neuropsychiatric damage.